Early Hypertrophic Signals After Myocardial Stretch : Role of Reactive Oxygen Species and the Sodium/Hydrogen Exchanger - Cingolani, Horacio Eugenio (2010)
In this chapter the enhanced activity of the cardiac Na+/H+ exchanger (NHE-1) after myocardial stretch is considered a key step of the intracellular signaling pathway leading to the slow force response to stretch as well as an early signal for the development of cardiac hypertrophy.We propose that the chain of events triggered by stretch begins with the release of small amounts of angiotensin II which in turn induce the release/formation of endothelin. The actions of these hormones trigger the production of mitochondrial reactive oxygen species that enhances NHE-1 activity, causing an increment in the intracellular Na+ concentration which promotes the increase in intracellular Ca2+ concentration ([Ca2+]i) through the Na+/Ca2+ exchanger. This [Ca2+]i increase would trigger cardiac hypertrophy by activation of widely recognized Ca2+-dependent intracellular signaling pathways.